Paradigma Dispensasi Perkawinan di Pengadilan Agama Muara Labuh Antara Maslahah dan Inkonsistensi Hukum - M. Novval Adhari Novval; Hanif Aidhil Alwana Hanif; Rio Wanda Saputra Rio (Hakamain: Journal of Sharia and Law Studies, 2022)
This paper illustrates the dispensation in the marriage law in Indonesia, because marriage is a complex Muslim act, containing elements of worship and muamalah which in practice will always experience influence according to the circumstances of the bridegroom and prospective bride. The existence of a marriage dispensation reaps the pros and cons among the Judges throughout the Religious Courts, it is evident in each of the Religious Courts in Indonesia that have absolute authority in examining and adjudicating cases resulting in diverse stipulations, both to grant, or reject the petition of the applicant. Specifically in this study it was found that the number of registered marriage dispensation cases had doubled from the previous year, in 2016 there were 3 cases while in 2017 there were 6 cases. The conclusion in this study is the presence of marital dispensation is a casuistic option for the person who have a desire to get married immediately; protect themselves from immorality, the emergence of life motivation in boosting the economy; low education, low religious understanding, promiscuity; unwed pregnant. Whereas in conducting legal considerations in this case, the Judge uses the concept of maslahah, and also avoids the applicant from continuing immorality.